Association Between Insurance Status and Patient Safety in the Lumbar Spine Fusion Population - Tanenbaum, Joseph E. (Spine J, 2016)
BACKGROUND CONTEXT: Lumbar fusion is a common and costly procedure in the United States. Reimbursement for surgical procedures is increasingly tied to care quality and patient safety as part of value-based reimbursement programs. The incidence of adverse quality events among lumbar fusion patients is unknown using the definition of care quality (patient safety indicators [PSI]) utilized by the Centers for Medicare and Medicaid Services (CMS). The association between insurance status and the incidence of PSI is similarly unknown in lumbar fusion patients. PURPOSE: This study sought to determine the incidence of PSI in patients undergoing inpatient lumbar fusion and to quantify the association between primary payer status and PSI in this population. STUDY DESIGN: Retrospective cohort study. PATIENT SAMPLE: All adult patients aged eighteen years and older included in the nationwide inpatient sample (NIS) that underwent lumbar fusion from 1998–2011. OUTCOME MEASURES: Incidence of one or more PSI, a validated and widely used metric of inpatient healthcare quality and patient safety. METHODS: NIS data were queried for all cases of inpatient lumbar fusion from 1998–2011. Incidence of adverse patient safety events (PSI) was determined using publicly available lists of ICD-9-CM diagnosis codes. Logistic regression models were used to determine the association between primary payer status (Medicaid/self-pay relative to private insurance) and the incidence of PSI. RESULTS: 539,172 adult lumbar fusion procedures were recorded in the NIS from 1998–2011. Patients were excluded from the secondary analysis if “other” or “missing” was listed for primary insurance status. The national incidence of PSI was calculated to be 2,445 per 100,000 patient years of observation, or approximately 2.5%. In a secondary analysis, after adjusting for patient demographics and hospital characteristics, Medicaid/self-pay patients had significantly greater odds of experiencing one or more PSI during the inpatient episode relative to privately insured patients (OR 1.16 95% CI 1.07 – 1.27). CONCLUSION: Among patients undergoing inpatient lumbar fusion, insurance status is associated with the adverse healthcare quality events used to determine hospital reimbursement by CMS. The source of this disparity must be studied to improve the quality of care delivered to vulnerable patient populations.